Hollowing Out : The Channels of Income Polarization in the United States - Alichi, Ali.; Mariscal, Rodrigo; Muhaj, Daniela (Washington, D.C. : International Monetary Fund, 2017)
Data show that middle-income households have continued moving down, and less so up, the income distribution in the United States since the 1970s-a phenomenon that is often referred to as the polarization or 'hollowing out' of the income distribution. While the level of income polarization is generally lower in the richer states (i.e., those with higher median household income levels), there have been wide variations in the changes in income polarization over time across states. The paper develops two indices to measure income polarization including a novel hollowing-out index. Another important contribution of the paper is to examine the proximate causes of income polarization. The econometric analysis is done at both state and household levels. The results suggest that technology, measured by job routinization, and international trade, measured by job offshoring, can fully explain the non-trend rise in income polarization, with broadly equal contributions. Household characteristics, including age, education, race, and gender have also been important drivers but with a net countervailing effect on income polarization. This is mainly thanks to the rising education level of households, which has led to better incomes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet